Karakteristik Fisik Wol Domba Batur dan Domba Garut - Umizakiah, K.; Yamin, M.; Soenarno, M. S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2014)
Batur sheep produce medium wool, while garut sheep produce coarse wool. Knowledge about wool physical characteristics of both breeds are important due to the potential background forutilization to certain product.  The aims of this research were to indentify and compare wool physical characteristics of batur sheep (WB) and garut sheep (WG). The variables observed including bundle tenacity, elongation, flammability, sound and thermal insulation properties. The comparison data of sound and thermal insulation ability between board (P), board + batur sheep wool (PWB), and board + garut sheep wool (PWG) were designed by Completely Randomized Design (CRD) and analyzed by using the Analysis of Variance (ANOVA) as well as the comparison data of flammability between WB, WG, P and nylon.  The comparison data of bundle tenacity, elongation, sound and thermal insulation properties between board + batur sheep wool (PWB), and board + garut sheep wool (PWG) were analyzed by T-test.  The result showed that WB and WG had no significant difference on their tenacity, resilient, and flammability (P > 0.05).  PWB and PWG had better sound and thermal insulation ability compared than P.  Wol had flammability better than P and nylon.